Congenital agminated Spitz nevus. - Castillo Molina, D.; Blanco Gómez, J.; Muñoz Ordóñez, S.; Bernal Alfonso, S.; Klyn, M.; Morales, S.D.; Castillo, D.E. (European Journal of Pediatric Dermatology, 2025)
Spitz nevus is a melanocytic nevus that is more frequent in pediatric age, in some cases present at birth. Its clinical and histological characteristics are variable and can represent a challenge for the dermatologist and the pathologist. We describe the case of a two-year-old child who has had since birth on the right thumb an erythematous-violet plaque with an irregular surface and with secondary alterations of the nail plate. The lesion, according to the parents, has undergone recurrent episodes of bleeding. The histological examination speaks of a low-risk Spitz nevus. The lesion is treated with cryotherapy, which reduces its thickness and clinical evidence.